FORMULATION OF SHRIMP COOKIES USING WHITE SHRIMP (PENAEUS VANNEMEI) CRUST POWDER ENRICHED WITH COCONUT WATER - Castro, Charena J (Journal of Agriculture and Technology Management, 2022)
Shrimp crust or shell contains protein, chitin, and minerals. As such, they could be good additives in various food items because of their nutritional value. This study presents the method of preparing shrimp cookies using white shrimp crust powder with varying concentrations of coconut water as pretreatment. Sensory qualities of coconut-water treated cookies using preference and descriptive testing and microbial analyses were done. Based on the ANOVA at a 5% significance level, shrimp crust treated with 25% brine solution and 75% coconut water gave the highest mean score of 8.11, which means “like very much.” The sensory panelists described the cookies with 3g coconut-water-treated shrimp crust powder as the most preferred treatment formulation with a golden-brown color, slight shrimp flavor, moderate shrimp odor, and crunchy texture. The most preferred cookie has a bacterial aerobic plate count of < 1.0 x 10 2 cfu/g and minimal counts of Escherichia coli , Staphylococcus aureus, mold, and yeast. The proximate analysis of the cookies has an ash content (1.09%), moisture content (1.53%), total fat content (17.4%), protein content (9.82%), and carbohydrates content (70.2%). Hence, cookies can contain 3g shrimp crust powder using 25% chilled brine solution and 75 % coconut water as a pretreatment method for the crust. The product is viable for community and university enterprises.